Digital Accounting, MSME Financing, and Economic Growth A PRISMA-Based Systematic Literature Review, Bibliometric Analysis, and VOSviewer Mapping - Muh. Ridwan Hayadin; Muh. Ilhamuddin Dahri; Nurul Listiawati; Indayani Indayani; Nur Qamariah. S (Sean Institute, 2026)
Digital accounting transformation has reshaped how micro, small, and medium enterprises (MSMEs) record, process, and communicate financial information, while opening new pathways to access financing and contributing to economic growth. This study maps the intellectual structure and thematic evolution of the literature linking digital accounting, MSME financing, and economic growth through a Systematic Literature Review (SLR) based on the PRISMA 2020 protocol, combined with bibliometric analysis and VOSviewer network mapping. The final corpus comprised 54 Scopus-indexed documents published between 2005 and 2026, including journal articles, conference papers, and book chapters. Performance analysis revealed a marked acceleration in scientific output since 2023, with Indonesia, Jordan, Malaysia, and Saudi Arabia emerging as the leading contributors, and a total of 859 citations concentrated in a small number of influential works. Keyword co-occurrence mapping identified six thematic clusters centred on accounting information systems, MSME financial performance, cloud-accounting adoption, decision-making, post-pandemic digital transformation, and system alignment and information quality. The temporal overlay revealed a shift in emphasis from conventional system-alignment issues towards digital accounting, artificial intelligence, and sustainability. The findings confirm that digital accounting serves as an enabler, improving financial information quality, reducing information asymmetry with finance providers, and strengthening MSMEs’ capacity for growth. This study contributes to a future research agenda that connects digital financial literacy, financial inclusion, and the macroeconomic effects of MSMEs in developing countries